Influence of vagal control on sex-related differences in left ventricular mechanics and hemodynamics - Williams, Alexandra M.; Shave, Rob E.; Coulson, James M.; White, Harriet; Rosser-Stanford, Bryn; Eves, Neil D. (American journal of physiology. Heart and circulatory physiology, 2018)
Left ventricular (LV) twist mechanics differ between men and women during acute physiological stress, which may be partly mediated by sex differences in autonomic control. While men appear to have greater adrenergic control of LV twist, the potential contribution of vagal modulation to sex differences in LV twist remains unknown. Therefore, the present study examined the role of vagal control on sex differences in LV twist during graded lower body negative pressure (LBNP) and supine cycling. On two separate visits, LV mechanics were assessed using two-dimensional speckle-tracking echocardiography in 18 men (22 ± 2 yr) and 17 women (21 ± 4 yr) during −40- and −60-mmHg LBNP and 25% and 50% of peak supine cycling workload with and without glycopyrrolate (vagal blockade). LV twist was not different at baseline but was greater in women during −60 mmHg in both control (women: 16.0 ± 3.4° and men: 12.9 ± 2.3°, P = 0.004) and glycopyrrolate trials (women: 17.7 ± 5.9° and men: 13.9 ± 3.3°, P < 0.001) due to greater apical rotation during control (women: 11.9 ± 3.6° and men: 7.8 ± 1.5°, P < 0.001) and glycopyrrolate (women: 11.6 ± 4.9° and men: 7.1 ± 3.6°, P = 0.009). These sex differences in LV twist consistently coincided with a greater LV sphericity index (i.e., ellipsoid geometry) in women compared with men. In contrast, LV twist did not differ between the sexes during exercise with or without glycopyrrolate. In conclusion, women have augmented LV twist compared with men during large reductions to preload, even during vagal blockade. As such, differences in vagal control do not appear to contribute to sex differences in the LV twist responses to physiological stress, but they may be related to differences in ventricular geometry. NEW & NOTEWORTHY This is the first study to specifically examine the role of vagal autonomic control on sex-related differences in left ventricular (LV) mechanics. Contrary to our hypothesis, vagal control does not appear to primarily determine sex differences in LV mechanical or hemodynamic responses to acute physiological stress. Instead, differences in LV geometry may be a more important contributor to sex differences in LV mechanics.